2012
DOI: 10.1371/journal.pone.0041802
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SCN1A and PCDH19 Mutations in Chinese Children with Dravet Syndrome

Abstract: BackgroundDravet syndrome is a severe form of epilepsy. Majority of patients have a mutation in SCN1A gene, which encodes a voltage-gated sodium channel. A recent study has demonstrated that 16% of SCN1A-negative patients have a mutation in PCDH19, the gene encoding protocadherin-19. Mutations in other genes account for only a very small proportion of families. TSPYL4 is a novel candidate gene within the locus 6q16.3-q22.31 identified by linkage study.ObjectiveThe present study examined the mutations in epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 49 publications
2
50
0
2
Order By: Relevance
“…83 In a study with 18 Dravet syndrome cases, 15 (83%) had SCN1A mutations (7 truncating, 2 splice site, and 6 missense mutations), which showed that truncating/splice site mutations were associated with moderate to severe intellectual disability in these subjects. 84 Gamma aminobutyric acid (GABA) is the primary inhibitory neurotransmitter in the central nervous system. The gamma aminobutyric acid type A (GABAA) receptor channel is the major postsynaptic receptor for GABA.…”
Section: Dravet Syndromementioning
confidence: 99%
“…83 In a study with 18 Dravet syndrome cases, 15 (83%) had SCN1A mutations (7 truncating, 2 splice site, and 6 missense mutations), which showed that truncating/splice site mutations were associated with moderate to severe intellectual disability in these subjects. 84 Gamma aminobutyric acid (GABA) is the primary inhibitory neurotransmitter in the central nervous system. The gamma aminobutyric acid type A (GABAA) receptor channel is the major postsynaptic receptor for GABA.…”
Section: Dravet Syndromementioning
confidence: 99%
“…(2009) описали 1 паци-ента с синдромом Драве и гомозиготной мутацией в гене SCN1B [7]. Также геном-кандидатом, который может вызывать клинику синдрома Драве, считается TSPYL4 [12].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…Dravet syndrome is classified as a severe form of epilepsy that results from a genetic mutation in the alpha-subunit of the sodium channel SCN1A [62][63][64]. In some cases of Dravet syndrome, genetic mutations cause the inactivation of one copy of the gene, known as haplo-insufficiency, in which there is only one functional copy.…”
Section: Epilepsy In Childrenmentioning
confidence: 99%